2015
DOI: 10.1128/aac.01183-15
|View full text |Cite
|
Sign up to set email alerts
|

ELQ-300 Prodrugs for Enhanced Delivery and Single-Dose Cure of Malaria

Abstract: f ; Medicines for Malaria Venture, Geneva, Switzerland g ELQ-300 is a preclinical candidate that targets the liver and blood stages of Plasmodium falciparum, as well as the forms that are crucial to transmission of disease: gametocytes, zygotes, and ookinetes. A significant obstacle to the clinical development of ELQ-300 is related to its physicochemical properties. Its relatively poor aqueous solubility and high crystallinity limit absorption to the degree that only low blood concentrations can be achieved fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 13 publications
1
69
0
Order By: Relevance
“…Pyrimidine biosynthesis is coupled to the respiratory chain by the participation of ubiquinone in the reoxidation of DHODH, and the electrons generated from dihydroorotate oxidation are transferred into the respiratory chain (24). T. gondii and blood stages of malaria parasites both require mitochondrial metabolism, because these parasites are highly susceptible to inhibitors of cytochrome bc 1 (complex III), such as atovaquone (36)(37)(38), that inhibit electron transport through the essential respiratory chain (39)(40)(41). Recent studies on mammalian DHODH have shown that DHODH is physically associated with the respiratory chain complexes III and II (42).…”
Section: Discussionmentioning
confidence: 99%
“…Pyrimidine biosynthesis is coupled to the respiratory chain by the participation of ubiquinone in the reoxidation of DHODH, and the electrons generated from dihydroorotate oxidation are transferred into the respiratory chain (24). T. gondii and blood stages of malaria parasites both require mitochondrial metabolism, because these parasites are highly susceptible to inhibitors of cytochrome bc 1 (complex III), such as atovaquone (36)(37)(38), that inhibit electron transport through the essential respiratory chain (39)(40)(41). Recent studies on mammalian DHODH have shown that DHODH is physically associated with the respiratory chain complexes III and II (42).…”
Section: Discussionmentioning
confidence: 99%
“…This implies that only low blood concentrations can be achieved following oral dosing. Pro-drug strategy represents a viable approach to improve bio-availability and overcome the physicochemical limitations of quinolone analogues to deliver the active drug at concentrations sufficient for safety, as well as achieving single-dose cures [88]. At the molar equivalent dose of 3 mg/kg of body weight, the delivery of ELQ-300, a endochin analogue from ELQ-337, its O-linked carbonate ester pro-drug, is enhanced by threefold to fourfold, reaching a maximum concentration of drug in serum [88].…”
Section: Anti-malarial Quinolonesmentioning
confidence: 99%
“…6 The third partner is logically constructed about the 4(1H)-quinolone scaffold. In addition to being used clinically against a variety of infectious diseases including tuberculosis, 7 certain quinolones have acquired lead status for development of drugs for treatment of toxoplasmosis 8,9 and malaria 10,11,12 respectively.…”
Section: Graphical Abstractmentioning
confidence: 99%
“…6 The third partner is logically constructed about the 4(1H)-quinolone scaffold. In addition to being used clinically against a variety of infectious diseases including tuberculosis, 7 certain quinolones have acquired lead status for development of drugs for treatment of toxoplasmosis 8,9 and malaria 10,11,12 respectively.Our attention is drawn to decoquinate (DQ, 1) that has been used for many years in veterinary medicine largely coadministered with poultry feed for treatment of coccidiosis wherein it displays negligible toxicity. 13,14 It is also used against other apicomplexan infections in animals 15 and is highly active in a murine model against Toxoplasma gondii.…”
mentioning
confidence: 99%